2017
DOI: 10.5121/ijaia.2017.8605
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Autoregressive Network with the Use of a Moving Average Method for Forecasting Typhoon Tracks

Abstract: Forecasting of a typhoon moving path may help to evaluate the potential negative impacts in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Gao et al [19] built a typhoon path prediction model based on LSTM (Long Short-Term Memory) and found that its error size is affected by the amount of data set and is more suitable for making short-term predictions of typhoon paths. Tienfuan Kerh et al [20] proposed a method that combines static and dynamic neural network models and treats the variables affecting the typhoon path as a time series and uses a nonlinear autoregressive network with a moving average method to predict the typhoon track, which provides a new idea and method for typhoon path prediction. In the literature [21], a classification and prediction method based on a gated unit recurrent neural network was proposed, and he first classified the typhoon using a dynamic regularization algorithm, and then the typhoon path was predicted using GRU.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [19] built a typhoon path prediction model based on LSTM (Long Short-Term Memory) and found that its error size is affected by the amount of data set and is more suitable for making short-term predictions of typhoon paths. Tienfuan Kerh et al [20] proposed a method that combines static and dynamic neural network models and treats the variables affecting the typhoon path as a time series and uses a nonlinear autoregressive network with a moving average method to predict the typhoon track, which provides a new idea and method for typhoon path prediction. In the literature [21], a classification and prediction method based on a gated unit recurrent neural network was proposed, and he first classified the typhoon using a dynamic regularization algorithm, and then the typhoon path was predicted using GRU.…”
Section: Introductionmentioning
confidence: 99%